1986
DOI: 10.1111/j.1600-0528.1986.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions in adults, 35–44 years of age: an overview of CPITN data in the WHO Global Oral Data Bank

Abstract: Results of 28 CPITN surveys in 24 countries for the age group 35-44 years, stored in the WHO Global Oral Data Bank as of 1 July 1986 are assembled in an overview presenting: percentages of persons according to the highest score for each person, the estimated national percentages of edentulousness and the mean numbers of sextants affected per person. It is concluded that for a large majority in most of the populations observed, the progress of periodontal disease has been slow and seems to be compatible with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
34
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 0 publications
11
34
1
Order By: Relevance
“…These results are in line with previous multi‐country comparisons (Pilot et al. , Albandar & Rams , Petersen & Ogawa ) and a recent systematic review where the prevalence of severe periodontitis was higher in South Asian and African countries compared to the UK (Kassebaum et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with previous multi‐country comparisons (Pilot et al. , Albandar & Rams , Petersen & Ogawa ) and a recent systematic review where the prevalence of severe periodontitis was higher in South Asian and African countries compared to the UK (Kassebaum et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…The same prevalence of periodontitis was reported from Bangladesh, Burkina Faso, Kenya, Libya, and Nepal. [8] The prevalence of periodontitis (90%) in the present study was different from the prevalence (27%) reported by Joseph and Cherry[3] in Trivandrum. The main reasons were the age of the population and oral hygiene habits.…”
Section: Discussioncontrasting
confidence: 97%
“…A recent study on the periodontal conditions in adults 35^14 yr old (14) using the WHO Global Oral Bank and basing on the Community Periodontal Index for Treatment Needs (3) revealed that the industrialized countries yielded between 4% and 18% of this age group in need of comprehensive periodontal care. The results of the present survey suggest sub-stantially higher percentages (55%) if the subjects between 30 and 49 yr of age with at least one site of probing depth of 6 mm or more were screened for.…”
Section: Discussionmentioning
confidence: 99%